MODEL PENGUKURAN EFEKTIFITAS PERALATAN PENUNJANG PADA GEDUNG BERTINGKAT MILIK PERGURUAN TINGGI DENGAN METODE OEE (STUDI KASUS: LIFT DI UNIVERSITAS XX) (Universitas Esa Unggul, 2017)
Colleges using high-rise buildings for the teaching and learning process are faced with the high level of damage suffered by the lifts. This happens because when the learning process progresses, the elevator users are filled with many students in a number and at the same time causing the elevator to often experience high loads and sometimes excessive (overload) resulted in frequent damage. A case study on this study was conducted at the University of XX located at Kebon Jeruk Jakarta Barat. Based on the reference and discussion with the manager of the elevator, to measure the effectiveness of elevators need to calculate the magnitude of Availability value, Performance Efficiency, and Rate of Quality Services. Availability is influenced by downtime losses with the variable Equipment Failure and Set up â€“ Adjusment. Performance Efficiency is influenced by Speed Losses with the variable Idling and Minor Stoppage and Reduced Speed variables. The value of Rate of Quality Services is influenced by Defect Losses with the variable Process Defect and Reduce Yield. Data on elevator interval measurement is obtained in 2 (two) building A and C of the XX campus and several other campuses are high-rise at the University of Mercu Buana Jakarta and in the Faculty of Engineering University of Indonesia Depok. The calculation results show for building A which has 8 floors, in 5 minutes the number of people to be transported (5HC) as much as 16.52%. With a population density of 3.8 m2 per-person (much more dense than the standard office that is 11 m2 per-person), the total number of people in the building 3450 people (peak load time), as well as the length of time the elevator interval per-floor is 31 seconds (speed is influenced by the setting of the sensor on the lift) then requires 55 lifts. The C building has 5 floors, in 5 minutes the number of people to be transported (5 HC) as much as 12%. Population density 7.7 m2 per-person, total number of people in the building 500 people (peak load time), as well as the length of time the elevator interval per-floor is 31 seconds then requires 2.48 lifts.Â Keywords: Overall Equipment of Effectiveness (OEE), lifts, Overload, Availability, Performance Efficiency, and Rate of Quality Service.